Association of Serum Fetuin-A Levels with Allograft Outcome in Renal Transplant Recipients - Mehrsai, Abdolrasoul; Pourmand, Gholamreza; Azhdari Tehrani, Hamed; Keyhan, Hossein; Rahmati, Mohamad Reza; Ahmadi, Ayat; Dehghani, Sanaz; Mashhadi, Rahil (Urology Journal, 2015)
Purpose: To determine serum fetuin-A pattern after renal transplantation and its association with graft outcome. Materials and Methods: In 41 renal transplant recipients, serum pretransplant fetuin-A levels and serum fetuin-A concentrations on days 7 and 30 after transplantation were measured using the enzyme-linked immunosorbent assay (ELISA) method. Also, the association between serum fetuin-A levels with clinical and laboratory parameters was evaluated. Results: A significant decrease in serum fetuin-A levels was noted in the first week after transplantation (P < .001). Subsequently, it started to increase and surpass pretransplant values during the first month (P < .001). Pretransplant fetuin-A levels did not differ among patients with different diethylenetriamine pentaacetic acid (DTPA) results. In addition, serum fetuin-A levels did not significantly correlate with metabolic parameters. Conclusion: In this prospective study there was no increase in serum fetuin-A levels during the first month and pretransplant fetuin-A levels are not predictive for allograft outcome in renal transplant recipients.